2020
DOI: 10.1038/s41598-020-69431-y
|View full text |Cite
|
Sign up to set email alerts
|

Virtual screening identifies broad-spectrum β-lactamase inhibitors with activity on clinically relevant serine- and metallo-carbapenemases

Abstract: Bacteria are known to evade β - lactam antibiotic action by producing β-lactamases (BLs), including carbapenemases, which are able to hydrolyze nearly all available β-lactams. The production of BLs represents one of the best known and most targeted mechanisms of resistance in bacteria. We have performed the parallel screening of commercially available compounds against a panel of clinically relevant BLs: class A CTX-M-15 and KPC-2, subclass B1 NDM-1 and VIM-2 MBLs, and the class C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 64 publications
(78 reference statements)
8
29
0
Order By: Relevance
“…[35] We initiated a discovery and optimization program of MBL inhibitors based on the 1,2,4-triazole-3-thione scaffold, after the discovery by Otto Dideberg's group of its original binding mode in the active site of the di-zinc subclass B3 MBL L1, i. e. a simultaneous coordination of the two Zn ions by the N 2 (Zn1) and S 3 (Zn2) atoms of the heterocyclic moiety. [36] A similar binding mode was more recently reported in the case of the dizinc subclass B1 MBLs VIM-2 [37][38][39] and NDM-1. [39] It is also noteworthy that several studies reporting random virtual and experimental screenings for MBL inhibition retrieved compounds containing this heterocycle in the case of L1, [40] IMP-1, [41] VIM-2 [37,39] and NDM-1.…”
Section: Introductionsupporting
confidence: 82%
“…[35] We initiated a discovery and optimization program of MBL inhibitors based on the 1,2,4-triazole-3-thione scaffold, after the discovery by Otto Dideberg's group of its original binding mode in the active site of the di-zinc subclass B3 MBL L1, i. e. a simultaneous coordination of the two Zn ions by the N 2 (Zn1) and S 3 (Zn2) atoms of the heterocyclic moiety. [36] A similar binding mode was more recently reported in the case of the dizinc subclass B1 MBLs VIM-2 [37][38][39] and NDM-1. [39] It is also noteworthy that several studies reporting random virtual and experimental screenings for MBL inhibition retrieved compounds containing this heterocycle in the case of L1, [40] IMP-1, [41] VIM-2 [37,39] and NDM-1.…”
Section: Introductionsupporting
confidence: 82%
“…The compound simultaneously bound to the two Zn ions through two atoms of its heterocyclic moiety (N 2 for Zn1 and S 3 for Zn2). A similar binding was more recently established for the di-zinc subclass B1 MBLs VIM-2 [37,38] and NDM-1 [39]. It is also noticeable that several other studies, including random in silico and experimental screenings, identified this heterocycle as a potential scaffold for the inhibition of IMP-1 [40], VIM-2 [37] and NDM-1 [41].…”
Section: Introductionsupporting
confidence: 76%
“…Although less potent, the corresponding compound 39 significantly inhibited VIM-type enzymes. (38,39) was also compatible with inhibition of the same enzymes.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In MBLs, active site inhibitors can act, disrupting the active nucleophile in the active site or, more often, contain zinc coordinating moieties that may exert off-target toxicity in host zinc enzymes and can be limitedly modulated for adjusting the ADME profile [ 54 ]. Recent studies demonstrated that common inhibition strategies can be overcome by the design of non-covalent cross-class inhibitors able to affect the catalytic efficiency of both SBLs and MBLs [ 63 , 64 ]. However, the availability of allosteric inhibitors would be highly beneficial because of the potential synergistic effect with more “traditional” inhibitors, or for the restoration of β-lactam antibiotic activity.…”
Section: Allosteric Regulation In Bls: Potential Advantages and Chmentioning
confidence: 99%